Islamic Ethics of Waste Management towards Sustainable Environmental Health - Mohd Omar , Suhaila; Chowdhury, Ahmed Jalal Khan; Abdulahi Hashi, Abdurezak (IIUM Medical Journal Malaysia, 2018)
Islam is a religion that prescribes a way of life that goes beyond the rituals. It provides a holistic guide to human beings in almost every aspect of life in this world. However, the modernization and economic growth have taken the leads in the society governance and therefore tarnished some of the Muslim society’s perceptions on the holistic guidance of Islamic teachings. One of the consequences was readily displayed through attitudes and inefficient waste management practice of the majority of the Islamic country that lead to the environmental health problem. The paper discusses the existing waste management practice and positive roles of true Islamic understanding through the Qur’an and the Sunnah in terms of avoiding wasteful consumption and manners of cleanliness to resolve global environmental health problem caused by poor waste management.